Maturation capacity, morphology and morphometric assessment of human immature oocytes after vitrification and in-vitro maturation - Saeedeh Nazari; Mohammad Ali Khalili; Forouzan Esmaielzadeh; Mehdi Mohsenzadeh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: In general, 15% of oocytes collected in ART cycles are immature. These oocytes may be cryopreserved further for use in in-vitro maturation (IVM) program.Objective: The aim of this study was to determine maturation capacity, morphometric parameters and morphology of human immature oocytes in both fresh IVM (fIVM) and vitrified-IVM (vIVM) oocytes.Materials and Methods: 93 women who underwent controlled ovarian stimulation for ART were included. The immature oocytes (n=203) were divided into two groups: the first group (n=101) directly matured in vitro; and the second group (n=102) first vitrified, then matured in vitro. All oocytes underwent IVM in Ham's F10 supplemented with LH+FSH and human follicular fluid. After 48h of incubation, the oocyte maturation rates, as well as morphometric and morphologic characteristics were assessed using cornus imaging and were compared. Results: Oocyte maturation rates were reduced in vIVM, (40.4%), in comparison with fIVM (59.4%, p<0.001). Following morphometric assessment, there was no difference in the mean oocyte diameters (µm) between fIVM and vIVM, 156.3±6.8 and 154.07±9.9, respectively. Other parameters of perimeters, egg areas, as well as oocyte and ooplasm volumes were similar in two groups. In addition, more morphologic abnormalities, such as, vacuole, and dark oocyte were observed in vIVM oocytes.Conclusion: fIVM was more successful than vIVM groups. No statistical differences were noticed in morphometry assessment in two groups. This suggests that morphometric parameters can not be applied as prognosis factor in oocyte maturation outcome in IVM program